Bmp5 Mutation Alters mRNA Expression During External Ear Development. Issue 2 (27th March 2023) - Liu, Wei; Lin, Lin; Sun, Yiwei; Jin, Shengyang; Yang, Qinghua; Jiang, Haiyue
Abstract : To understand changes in gene regulation and mRNA expression in external ear development, we used a bone morphogenetic protein 5 (BMP5) short-ear mouse model. External ear tissues at E15.5 and E17.5 were collected, and mRNA expression profiles were analyzed. Upregulated and downregulated mRNA expression was identified using find_circ and CIRI2 software. Gene Ontology and Kyoto Encyclopedia of Genes and Genomes enrichment analyses were performed using the differentially expressed mRNAs. Alterations in related signal pathways were identified from the upregulated and downregulated mRNA transcripts. The results showed a correlation between the mRNA expression during external ear development in BMP5 short-ear mice, including key regulatory mRNA changes after point mutations of the Bmp5 gene. This study provides evidence for the mechanism underlying mRNA regulation during external ear development. Changes in mRNA expression profiles also provide clues for future studies regarding the regulatory mechanisms underlying external ear development.